PEMBELAJARAN MENGANALISIS TEKS DESKRIPSI MODEL NUMBERED HEAD TOGETHER PADA SISWA KELAS VII SMP SIVALIPUTTA - Iswanto, Wawan; Muzammil, Ahmad Rabi’ul; Syahrani, Agus (Universitas Tanjungpura, 2022)
AbstractThis study provides an overview of the application of the numbered head together model in learning to analyze content and the supporting factors of the NHT model in descriptive text learning. The results of this study indicate that the application of the NHT model in learning to analyze the content of descriptive text is carried out in four meetings and includes six activities. In 1-3 meetings, preparatory activities, group formation, problem discussions, questions and answers, giving conclusions, and awards were carried out during the learning process to analyze the content of the descriptive text including: type, structure and language in the waterfall description text. The 4th meeting was held to assess the results of the individual analysis of the descriptive text entitled The Beauty of the Blue Lake among the Hills. The factors that support the success of learning are: competent teachers and careful planning stages in lesson plans, students who are enthusiastic about learning to analyze the content of descriptive texts, learning objectives that make students like descriptive texts, learning materials that are close to students, NHT methods, various media learning, learning evaluation of processes and products. Keywords: Analyze, Descriptive Text, Numbered Head Together.